Testes de aptidão musical em cursos de licenciatura em música: desnaturalização do conceito e suas implicações em ações educativo-musicais - Silva, Eduardo Teixeira da (2019)
The approach about musical aptitude shows a wide field of concepts that orbit the debate on the subject, revealing how much ambiguous can be its understanding in the field of Musical Education. This subject is approached using terms such as gift, talent, musicality, ability etc., in a way that is difficult to demarcate clearly the subtle understanding that each one of these words has. Therefore, an empirical perception was presented as a starting point of this investigation that problematizes the concept of musical aptitude as being pervaded by an apparent paradox in its conception, manifested by the definition of aptitude being presented both by innate and acquired disposition to a determined activity. In other words: some people are born predisposed to make music while others need to acquire such aptitude. Suggested such problem, this proposal of research had as a central objective to analyze the different meanings assumed, in several contexts, in the application of musical aptitude tests in graduations of music in Brazil. With this intention, it was adopted a multi-theoretical immersion that pervades different references on the subject, however, adopting a historiccultural perspective, due to the fact that it deals in a much satisfactory way with the question innate-acquired, that is in the core of the discussion about aptitude. This qualitative research was characterized as being essentially bibliographic and documentary, searching to access the production of articles, dissertations, thesis and books about the subjects that constituted its object, and the documents that approach the subject. As a result, we can highlight that the historic-cultural approach contributed to achieve the deconstruction of points of view that reproduce a mystified vision about music and musicians, building a historicized comprehension of musical aptitude and the terms related to it, important to oppose the harmful utilization that its use may have in educational-musical actions, such as the exclusion of subjects classified as devoid of aptitude for the accomplishment of music. Starting from the analysis of the context of the application of tests of specific abilities in graduations of music, it was concluded that the application of these exams would be neither ethic or just, as they demand acquirements that still are restricted to a limited part of the Brazilian population, because there still are no democratic access to scholar musical training as a practice of social justice as equity to the right to education in Brazil.